The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7869/tg.203
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation: a risk factor for development of hepatorenal syndrome in cirrhotic patients with acute variceal bleeding

Abstract: Background: This study aimed to assess whether QT interval prolongation is an independent risk factor for development of hepatorenal syndrome (HRS) in cirrhotic patients with acute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They also noted that the difference between these two values was an independent risk factor in predicting Hepatorenal syndrome. In this respect, they argued that QTc was a good tool in predicting the severity of cirrhosis and the risk of bleeding (13).…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that the difference between these two values was an independent risk factor in predicting Hepatorenal syndrome. In this respect, they argued that QTc was a good tool in predicting the severity of cirrhosis and the risk of bleeding (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, these interesting results must be confirmed by larger prospective observational studies, because this association may merely reflect that QT intervals generally correlate with degree of liver dysfunction, ie, more advanced cirrhosis shows greater prolongation of QTc. Peter and colleagues demonstrated that QTc, serum Na + concentration and β-blocker use predicted development of hepatorenal syndrome in 78 consecutive patients admitted with variceal bleeding 32 . However, as there were only 14 cases of hepatorenal syndrome (HRS), this small study needs to be confirmed by larger trials.…”
Section: Nsbb Decrease Electrocardiographic Qt Intervalsmentioning
confidence: 99%